Critical Faculty and Peer Instructor Development: Core Components for Building Inclusive STEM Programs in Higher Education - von Vacano, Claudia; Ruiz, Michael; Starowicz, Renee; Olojo, Seyi; Moreno Luna, Arlyn Y.; Muzzall, Evan; Mendoza-Denton, Rodolfo; Harding, David J. (Frontiers in Psychology, 2022)
First-generation college students and those from ethnic groups such as African Americans, Latinx, Native Americans, or Indigenous Peoples in the United States are less likely to pursue STEM-related professions. How might we develop conceptual and methodological approaches to understand instructional differences between various undergraduate STEM programs that contribute to racial and social class disparities in psychological indicators of academic success such as learning orientations and engagement? Within social psychology, research has focused mainly on student-level mechanisms surrounding threat, motivation, and identity. A largely parallel literature in sociology, meanwhile, has taken a more institutional and critical approach to inequalities in STEM education, pointing to the macro level historical, cultural, and structural roots of those inequalities. In this paper, we bridge these two perspectives by focusing on critical faculty and peer instructor development as targets for inclusive STEM education. These practices, especially when deployed together, have the potential to disrupt the unseen but powerful historical forces that perpetuate STEM inequalities, while also positively affecting student-level proximate factors, especially for historically marginalized students.